Permasalahan kemahiran membaca dan menulis bahasa melayu murid-murid sekolah rendah di luar bandar - Abdul Rasid Jamian (Penerbit UKM, 2011)
Reading and writing skills are basic skills in Malay Language for primary school children. Mastery of these skills is important in order to achieve greater achievements in the coming years. Thus, this research aims to identify problems pertaining to reading and writing skills in Malay language among rural primary school children. The respondents for this research consist of 161 primary year 4 and 5 students in rural schools in Negeri Sembilan, Pahang and Sarawak. The research is a descriptive surveyconducted by using questionnaires which include information on students’background and problems faced in reading and writing skills. The research findings show that there are problems within the students in mastering reading and writing skills in Malay Language, among them; basic knowledge in reading and writing, the environment and the teachers’ teaching method. The research findings in problems related to reading skills show that students fail to understand the content of the text (min=3.40; sp=.71) and meaning of sentence (min = 3.24;sp=.60). The research findings in problems related to writing skills show that students could not differentiate upper and lower case letters through letter identification (min=3.62; sp=.62). They could not identify punctuations either (min=3.42; sp= .80). The conclusion is, to overcome this problem, remedial education is one way to help enhance the potential of students who have problems in reading and writing skills. Remedial programs at an early stage will give a more effective effect in the effort to strengthen the education system of our country